High entropy alloys as electrode material for supercapacitors: A review. (1st December 2021) - Hussain, Iftikhar; Lamiel, Charmaine; Ahmad, Muhammad; Chen, Yatu; Shuang, Shuo; Javed, Muhammad Sufyan; Yang, Yong; Zhang, Kaili
Highlight: A kind of new materials, high-entropy alloys (HEAs) as an electrode. Differences in charge storing mechanism in electrode materials. Differences in symmetric, hybrid, and asymmetric supercapacitors. Recent advances in HEAs as an electrode material. Critical points to be considered for HEAs as newborn electrode materials. Abstract: Energy storage devices play an important role in our daily lives. As a kind of new materials, high-entropy alloys (HEAs) avoid the traditional "base element" concept and display a variety of interesting and unusual properties. HEAs have been considered promising electrode materials for energy storage and conversion technologies due to their excellent mechanical, chemical, and physical properties. Herein, we report a review on basic supercapacitor, such as differences in charge storing mechanism of electric double layer capacitive (EDLC)-, pseudocapacitive-, and battery-type electrode materials; differences in symmetric, hybrid, and asymmetric supercapacitor devices; and recent advances in HEAs as an electrode material for supercapacitors. The aim of this review is to combine newly emerge HEAs electrode materials with the basic concepts of supercapacitor and avoid the inflating misinterpretation in between the different energy storage systems. We also suggest critical points to be considered for high performance nanostructured HEAs as newborn electrode materials. Graphical abstract: Image, graphical abstract